Knowledge, Attitudes and Practices of Ramadan Fasting in Pregnant Thai-Muslim Women - Saowanee Saro; Somchai Tanawattanacharoen (The Royal Thai College of Obstetricians and Gynaecologists, 2018)
Objectives: To assess the basic religious knowledge regarding the Islamic law, attitudes and practices of Ramadan fasting during pregnancy in Thai-Muslim women.Materials and Methods: Multicenter, cross-sectional descriptive study was conducted between July 2016 and January 2017 on 619 pregnant Muslim women at antenatal care clinic from six hospitals in the three southernmost provinces of Thailand. Non-probability convenient sampling technique and a questionnaire were used to collect data from pregnant women who had experienced pregnancy during Ramadan at least once in their lives. Results: Most participants (85.5%) reported to have knowledge regarding the Islamic law clear exemption from fasting for pregnant women, and the missed fasts must be completed later. Majority of pregnant women believed the fasting during pregnancy did no harm to maternal health. Overall, 87.1% observed fasting during pregnancy. Mean fasting days was 24.56 ± 5.66 days and 63.0% observed fasting between 21-30 days. Logistic regression analysis demonstrated that their age ≥ 35 years and Islamic education increased the fasting during pregnancy (Adjusted OR 2.478, 95%CI 1.174-5.230, p = 0.017 and 2.244, 95%CI 1.236-3.988, p = 0.006, respectively). The main adversities from Ramadan fasting during pregnancy were weakness and fatigue.Conclusion: Most pregnant women knew Islamic law clear exemption from fasting during pregnancy, however many of pregnant women preferred fasting during Ramadan and they believed the fasting during pregnancy did no harm to maternal health. Healthcare providers are required to understand the religious beliefs of Muslim pregnant women, and design the standard guideline about managing lifestyle changes of Ramadan fasting during pregnancy.